Hate Crime Reporting as a Successful Social Movement Outcome - McVeigh, Rory; Welch, Michael R.; Bjarnason, Thoroddur (American Sociological Review, 2003)
Variation in compliance with public policies across local settings is examined through an analysis of the number of reported hate crime incidents in United States counties. Particular attention is given to the role that activist organizations play in promoting, or impeding, compliance with public policies. Each hate crime reported to the federal government is conceptualized as a successful outcome of social movement mobilization. Drawing upon political mediation theory and Fine's model of discursive rivalry, the analysis shows how social movement resources, framing processes, political incentives, and features of local contexts combine to promote successful social movement outcomes. The presence of resourceful civil rights organizations in a county can lead to higher numbers of reported hate crimes, but the influence of civil rights organizations is contingent upon the political context and upon objective conditions that lend credibility to civil rights framing.